MicroRNA-212-3p regulates early neurogenesis through the AKT/mTOR pathway by targeting MeCP2. (July 2020) - Zhai, Kaihua; Liu, Boyu; Teng, Junfang
Abstract: Compelling evidence has implicated role of microRNAs (miRNAs) in neurogenesis. Methyl-CpG Binding Protein 2 (MeCP2) was a key contributor to neurological disease. This study investigated whether miR-212-3p affects early neurogenesis associated with MeCP2. Microarray-based gene expression profiling of neurogenesis was employed to identify differentially expressed genes. Next, miR-212-3p expression in neural progenitor cells (NPCs) was detected using in situ hybridization and immunofluorescence. Effect of miR-212-3p and MeCP2 on cell viability, β-tubulin III expression and the AKT/mammalian target of rapamycin (mTOR) pathway activity was examined with gain- and loss-of-function experiments. In vivo experiments were also performed to verify effects of miR-212-3p on nerve tube development. MiR-212-3p expression was decreased while MeCP2 expression was increased during differentiation of NPCs. MiR-212-3p targets MeCP2 and down-regulates its expression, which resulted in repressed cell differentiation, proliferation as well as blocked AKT/mTOR pathway activation, subsequently early neurogenesis was prevented. Furthermore, overexpression of miR-212-3p inhibited nerve tube development in vivo . Taken together, miR-212-3p could restrain early neurogenesis through the blockade of AKT/mTOR pathway activation by targeting MeCP2, suggesting a promising therapeutic target for neurogenic disorders. Highlights: Inhibiting MeCP2 prevents early neurogenesis. miR-212-3p targets MeCP2. miR-212-3p inhibits early neurogenesis. MiR-212-3p targets MeCP2 to inhibit AKT/mTOR pathway activation. This study proposes a theoretical basis for further understanding of neurogenesis.